The Impact of Health Insurance Schemes for the Informal Sector in Low- and Middle-Income Countries : A Systematic Review - Acharya, Arnab; Vellakkal, Sukumar; Taylor, Fiona; Masset, Edoardo; Satija, Ambika; Burke, Margaret; Ebrahim, Shah (Published by Oxford University Press on behalf of the World Bank, 2015)
This paper summarizes the literature on the impact of state subsidized or social health insurance schemes that have been offered, mostly on a voluntary basis, to the informal sector in low- and middle-income countries. A substantial number of papers provide estimations of average treatment on the treated effect for insured persons. We summarize papers that correct for the problem of self-selection into insurance and papers that estimate the average intention to treat effect. Summarizing the literature was difficult because of the lack of (1) uniformity in the use of meaningful definitions of outcomes that indicate welfare improvements and (2) clarity in the consideration of selection issues. We find the uptake of insurance schemes, in many cases, to be less than expected. In general, we find no strong evidence of an impact on utilization, protection from financial risk, and health status. However, a few insurance schemes afford significant protection from high levels of out-of-pocket expenditures. In these cases, however, the impact on the poor is weaker. More information is needed to understand the reasons for low enrollment and to explain the limited impact of health insurance among the insured.